2013
DOI: 10.1161/jaha.112.004713
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Upregulation of Apamin‐Sensitive Potassium Currents in Failing Human Ventricles

Abstract: BackgroundWe previously reported that IKAS are heterogeneously upregulated in failing rabbit ventricles and play an important role in arrhythmogenesis. This study goal is to test the hypothesis that subtype 2 of the small‐conductance Ca2+ activated K+ (SK2) channel and apamin‐sensitive K+ currents (IKAS) are upregulated in failing human ventricles.Methods and ResultsWe studied 12 native hearts from transplant recipients (heart failure [HF] group) and 11 ventricular core biopsies from patients with aortic steno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 38 publications
6
92
2
3
Order By: Relevance
“…The channels are found to be expressed at a higher level in atria compared with ventricles (6). Our findings have subsequently been supported by several different laboratories (9,(29)(30)(31)(32)(33). We further demonstrate that SK channels play critical roles in pacemaking cells (34).…”
Section: Computational Prediction Of α-Actinin2supporting
confidence: 82%
“…The channels are found to be expressed at a higher level in atria compared with ventricles (6). Our findings have subsequently been supported by several different laboratories (9,(29)(30)(31)(32)(33). We further demonstrate that SK channels play critical roles in pacemaking cells (34).…”
Section: Computational Prediction Of α-Actinin2supporting
confidence: 82%
“…Large variations of I KAS densities have also been observed in VMs 8, 15, 35. The mechanisms by which some cells had more I KAS than others remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies showed that both SK channel proteins and apamin‐sensitive SK currents ( I KAS ) are abundantly present in the atria, atrioventricular node, pulmonary vein, and ventricular myocytes (VMs) of different species and play an important role in repolarization and arrhythmogenesis especially in heart failure and myocardial ischemia 5, 6. In both normal and failing ventricles, prolongation of the pacing cycle length (PCL) further increases the importance of I KAS in repolarization 7, 8. However, the importance of I KAS in the His‐Purkinje system remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The atrial IKCa was formulated as a time-independent passive K + current whose conductance depends strongly on the intracellular calcium concentration, [Ca 2+ ]i, following a Hill equation [11], [12]. Parameterization was achieved by fitting experimental data from isolated ventricular myocytes from HF patients [11], to give Equation (1):…”
Section: Formulation Of Ikca In Heart Failurementioning
confidence: 99%
“…Parameterization was achieved by fitting experimental data from isolated ventricular myocytes from HF patients [11], to give Equation (1):…”
Section: Formulation Of Ikca In Heart Failurementioning
confidence: 99%